IMPLEMENTASI PROGRAM KELINIK BACA SEBEGAI UPAYA PEMBERENTASAN BUTA AKSARA PADA WARGABINAAN PERMASYARAKATAN DI LAPAS KELAS III RANGKASBITUNG - Nida Yamanda; Ahmad Fauzi; Yosi Badrio (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of the Reading Clinic Program as an effort to eradicate illiteracy among correctional inmates at Class III Rangkasbitung Correctional Institution. The research is motivated by the importance of literacy programs for inmates as a provision for social reintegration after release. The study employed a qualitative descriptive approach. The research subjects consisted of five inmates participating in the Reading Clinic Program, selected using purposive sampling technique. Data were collected through participatory observation, in-depth interviews, and documentation. Data analysis was conducted through the stages of data reduction, data presentation, and conclusion drawing, using source and technique triangulation to ensure data validity. The results showed that the implementation of the program using the peer tutoring method and gradual learning materials proved effective in improving participants' literacy skills. Supporting factors included the inmates' internal motivation, the patience of peer tutors, active support from officers, and the presence of the researcher as an intern. Obstacles encountered included shame, difficulty concentrating, easy forgetfulness, uncomfortable learning space, inappropriate book collections, lack of professional educators, and frequently changing schedules. The program's impacts included improved reading ability, increased self-confidence, discipline, and the growth of hope and optimism for the future. Thus, the Reading Clinic Program can serve as an effective literacy empowerment model for Class III correctional institutions in Indonesia.